To Study The Prevalence Of Tubal Obstruction As A Cause Of Infertility (International Journal of Food and Nutritional Sciences, 2022)
Background: Infertility is the inability to sustain a pregnancy in a woman with regular (2–3 times per week) unprotected sexual intercourse for a period of 1 year.This is a major public health problem that remains under recognised in Cameroon and most countries in sub-Saharan Africa. This study aimed at identifying the risk factors associated with tubal infertility in a tertiary hospital in Santosh University , Ghaziabad.Aim and Objective: To study the prevalence of tubal obstruction as a cause of infertilityMethodology: It was a hospital-based prospective observational study that involved all couples attending the Obstetrics and Gynecology department's out-patient clinic at Santosh Medical College and Hospital, Ghaziabad. An 18-month period, from January 2019 to June 2020, was used for the study's execution. 193 couples were solicited, but only 172 couples who met the inclusion criteria were enrolled in the study. Of the 193 couples that were recruited and investigated, 10 patients were not thoroughly probed, and 11 were lost to follow-up.Result: 23.2% of the male participants had abnormal sperm analysis results. In primary infertility, azoospermia was seen in 10.2%(10) of cases. 23.3% of primary infertility cases and 3% (2) of subsequent infertility cases showed oligospermia, respectively.Conclusion: Being a housewife, working for yourself, having a history of Chlamydia trachomatis, Mycoplasma infection, and uterine fibroid were all independently linked to tubal infertility. Additionally, tubal infertility was linked to a history of pelvic surgery and previous procedures, diabetes mellitus, and persistent pelvic pain. Tubal infertility was less common in young people, those in monogamous relationships, and those who used barrier means of contraception like the condom. To prevent tubal infertility, the goal of intervention will be the identification of these causes.